Thoracic imaging : pulmonary and cardiovascular radiology - Webb, W. Richard 1945- (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Thoracic Imaging, Second Edition, written by two of the world's most respected specialists in thoracic imaging, is the most comprehensive text-reference to address imaging of the heart and lungs. Inside you'll discover the expert guidance required for the accurate radiologic assessment and diagnosis of both congenital and acquired cardiovascular and pulmonary diseases. New topics in this edition include coronary artery CT, myocardial disease, pericardial disease, and CT of ischemic heart disease. This edition has a new full-color design and many full-color images, including PET-CT. A companion website will offer fully searchable text and images"--Provided by publisher.